Educational video of the risk on cigarette in increasing knowledge and attitude among "little doctors" at elementary school - Cecep Eli Kosasih; Tetti Solehati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Cigarettes are a big problem in Indonesia. Smoking becomes a habit for adult men, and even extends to children. Children become accustomed to seeing the smoking patterns of adults in their homes. It is risky for children to try smoking. Education in preventing the dangers of smoking can be done in various ways, one of which is using video media. This study aimed to find out the effect of video education on the level of knowledge about the dangers of smoking at the little doctor in elementary school students. A quasi-experimental research design with pre-test and post-test design was used in this study. The study was conducted at Bojong Asih Elementary School, Pasawahan Elementary School, Cangkuang Elementary School, and Leuwi Bandung Elementary School in 2017. The population in this study were all 4-6 grade students totaling 323 people. The sample used was total sampling. Students were given questionnaires before the intervention and then were given education about the dangers of smoking through a video, then given a questioner again to measure the level of knowledge about the dangers of smoking. Data analysis was performed using an analysis of the paired t-test. The result from this study was found that the average level of knowledge before the intervention was 2.6 (SD = 0.86). After the intervention there was a change in the level of knowledge to 2.87 (SD = 0.48). There was an influence of a video media intervention on students' knowledge (p = 0,000). This study found significant differences in the increase in average knowledge before and after the intervention period (p = 0.001). The local government needs support the students, from both the Health Officer and the Education Office as well as sub-district officials, village heads and principals for the sustainability of smoke-free programs in schools by using video as a means of educating students.AbstrakRokok merupakan masalah yang besar di Indonesia yang menjadi kebiasaan bagi pria dewasa, bahkan merambah ke anak anak. Anak menjadi terbiasa melihat pola merokok orang dewasa di rumahnya. Hal ini beresiko pada anak untuk mencoba merokok. Perlu adanya pencegahan bahaya rokok dengan memberdayakan dokter kecil. Edukasi dalam pencegahan bahaya merokok bisa dilakukan dengan berbagai cara salah satunya adalah dengan menggunakan media video. Penelitian ini bertujuan untuk Mengetahui pengaruh edukasi video terhadap tingkat pengetahuan tentang bahaya rokok pada dokter kecil di sekolah. Desain penelitian menggunakan quasi eksperimen dengan rancangan pre test dan post test. Penelitian dilakukan di SDN Bojong Asih, SDN Pasawahan, SDN Cangkuang, dan SDN Leuwi Bandung tahun 2017. Populasi pada penelitian ini adalah seluruh dokter kecil kelas  4-6 berjumlah 12 orang. Sample yang digunakan adalah total sampling. Dokter kecil diberikan quesioner sebelum intervensi kemudian diberikan edukasi tentang bahaya rokok melalui video, kemudian diberikan quisioner kembali untuk mengukur tingkat pengetahuan tentang bahaya rokok. Analisa data dilakukan dengan menggunakan analisis uji t dependent. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang bermakna rata rata tingkat pengetahuan antara  sebelum dan setelah intervensi pada dokter kecil dari 69 menjadi 89 (p = 0,027). Pada variabel sikap menunjukan terdapat perbedaan yang bermakna rata rata sikap pengetahuan antara  sebelum dan setelah intervensi pada dokter kecil dari 75 menjadi (p = 0,056).  Edukasi melalui video efektif dalam meningkatkan tingkat pengetahuan dan sikap anak. Perlunya dukungan dari pihak pemerintah daerah setempat baik dari Dinas Kesehatan dan Dinas Pendidikan serta aparat camat, kepala desa, dan kepala sekolah bagi keberlanjutan program bebas rokok di sekolah dengan menggunakan video sebagai sarana edukasi pada siswa dengan memberdayakan dokter kecil dalam program pelaksanaannya.